Formation of a Key Intermediate Complex Species in Catalytic Hydrolysis of NH3BH3 by Bimetal Clusters: Metal-Dihydride and Boron-Multihydroxy - Yan, W. J.; Zheng, Y. F.; Zhou, T. W.; Wang, G. Z.; Wang, D. D.; Yuan, H. K. (Frontiers in Chemistry, 2020)
The hydrolysis of AB (AB, NH3BH3) with the help of transition metal catalysts has been identified as one of the promising strategies for the dehydrogenation in numerous experiments. Although great progress has been achieved in experiments, evaluation of the B-N bond cleavage channel as well as the hydrogen transfer channel has not been performed to gain a deep understanding of the kinetic route. Based on the density functional theory (DFT) calculation, we presented a clear mechanistic study on the hydrolytic reaction of AB by choosing the smallest NiCu cluster as a catalyst model. Two attacking types of water molecules were considered for the hydrolytic reaction of AB: stepwise and simultaneous adsorption on the catalyst. The Ni and Cu metal atoms play the distinctive roles in catalytic activity, i.e., Ni atom takes reactions for the H2O decomposition with the formation of [OH]− group whereas Cu atom takes reactions for the hydride transfer with the formation of metal-dihydride complex. The formation of Cu-dihydride and B-multihydroxy complex is the prerequisite for the effectively hydrolytic dehydrogenation of AB. By analyzing the maximum barrier height of the pathways which determines the kinetic rates, we found that the hydride hydrogen transferring rather than the N-B bond breaking is responsible to the experimentally measured activation energy barrier.